Synthesis, Characterization, and Antimicrobial Evaluation of New Heterocyclic Compounds Bearing a Biologically Active Sulfadiazine Moiety - Jala Bahjat Ziwar (Zanco Journal of Pure and Applied Sciences, 2024)
The eco-friendly techniques were utilized for the straightforward synthesis of new heterocyclic compounds bearing the sulfadiazine moiety by employing ultrasound irradiation techniques. Initially, sulfadiazine (1) was subjected to diazotization, followed by a coupling reaction with an activated methylene group (ethyl acetoacetate) to yield a hydrazone compound (3). Subsequently, the coupling adducts (3) were reacted with ethyl benzoylacetate, benzyl hydrazine, thiosemicarbazide, and guanidine under ultrasound irradiation, leading to the formation of pyridazine (4), pyrazolines (5, 6), and pyrimidine (7), respectively. Furthermore, when pyrazoline compound (6) was treated with chloroacetone and bromoaceophenone under ultrasound conditions, thiazole compounds (6a) and (6b) were formed, respectively. Additionally, new derivatives (10) and (11) were synthesized through diazotizing compound (7), followed by coupling reactions with an activated methylene group (acetylacetone) and reactions with urea and thiourea, respectively, all under ultrasound conditions. All the synthesized compounds were characterized using spectroscopic techniques such as FT IR, 1H-NMR, and 13C-NMR spectra. The synthesized chemicals exhibited promising antimicrobial activities against human pathogenic bacteria strains (Escherichia coli and Staphylococcus aureus) and Candida albicans fungi, as assessed through the broth microdilution technique.